Sensory Characteristics of Restructured Fresh Fruit Composite Prepared from Jack Fruit (Artocarpus heterophylla L.) and Sapodilla (MaidMara achras Mill. Fosb.) - Sri Raharjo (Indonesian Association of Food Technologists, 2002)
Jack fruit and sapodilla are tropical fruits having sweet and distinctive flavor and attractive color. At present, consumers have limited choice for ready-to-eat fresh fruit products available in the market. The objective of this study was to determine the sensory characteristics of fresh fruit product composite prepared from combination ofjackfruit and sapodilla and restructured Using three different type of alginate. Three different type of alginates and two form of calcium lactate (encapsulated and non encapsulated) were used as binding ingredients. Ten panelists were employed to evaluate the freshly prepared fruit prodact composite for its taste, aroma, appearance, mouthfeel, and gel strength using a 5-point scoring. Type of alginate had no effect on the sensory properties of restructured fruit layers. However, the source of calcium in the form of encapsulated or not encapsulated powder showed significant effect on the appearence and gel strength. The fruit layers prepared using encapsulated Ca-lactate had less attractive appearence and weaker gel strength than the fruits restructured with free Ca-lactate. The two difference source of calcium had no significant effect on the products taste, aroma, and mouthfeel.